Analisis Semiotika Makna Pesan Motivasi pada Lirik Lagu "Evaluasi" Karya Hindia - Achmad, Egi Saefullah; Nuh, Mohammad (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This research aims to examine the meaning of the motivational messages present in the lyrics of the song 'Evaluasi' by Hindia. A qualitative method based on Ferdinand de Saussure's concept of semiotic analysis is used, and a constructivist perspective serves as the theoretical framework. The results of the research show that the song lyrics from "Evaluasi" by Hindia and the signifier aspects found are the result of interpretation of the lyrics of the song "Evaluasi" by Hindia. The meaning of the motivational message is found in the lyrics of the song "Evaluasi" by Hindia. Stated in the problem formulation, the type of motivation is divided into two and the one used in the lyrics of the song "Evaluation" is the type of intrinsic motivation which is found throughout the song from verse 1 (one) to verse 8 (eight). The type of meaning found in the lyrics of the song "Evaluasi" is dominated by the connotative meaning found in stanza 1 (one), stanza 3 (three), stanza 4 (four), and stanza 5 (five). In conclusion, the type of meaning in the song "Evaluation" is connotative meaning. The type of message found is a persuasive message. In general, the song "Evaluasi" by Hindia has a connotative meaning, with intrinsic motivation and a persuasive message. Keywords: Semiotics, Meaning, Message, Motivation